Exploring Aggression Across Multiple Variables : A Review (International Journal of Scientific Research in Science and Technology, 2024)
Aggression is a common human emotion experienced regularly by most people. However, if not effectively managed, this emotion can be quite dangerous in both personal and professional contexts. As it is a natural emotion, it can be provoked by various factors (frustration, stress, fear, etc). Through a comparative approach, we explore variations in the ways aggression is manifested and its impact on individuals and their surroundings. This condones many types of anger, including verbal, physical, and passive-aggressive behavior. Therefore, by comparing studies on aggressiveness, we may gain a deeper knowledge of this complicated human emotion and draw useful conclusions for professionals and individuals who want to deal with aggression in both their private and professional lives. This is a comprehensive study between comparison of aggression levels of males and females which can guide us from a Forensic perspective to unleash the percentage of aggression according to the age which subject holds.
Keywords: Aggression; Aggressive behavior; Comparative study; Peer Aggression